Dynamic Simulation of Low-Carbon Competitiveness from the Perspective of Circular Economy - Xing Li; Fuzhou Luo (Complexity)
In accordance with the requirements of the circular economy in Guangxi (of PRC) and the characteristics of the drivers of low-carbon competitiveness in the regional construction industry, a causal flowchart of influencing factors of the low-carbon competitiveness in the Guangxi construction industry is constructed, and a model based on system dynamics is established. After the entropy weight method is used to determine the variable weight, VENSIM PLE software is used to simulate the development trend of the low-carbon competitiveness of the Guangxi construction industry. The simulation results of the promotion effect of various factors on the development of the low-carbon competitiveness of the regional construction industry from 2010 to 2020 are obtained, and countermeasures and suggestions are proposed from the perspective of a circular economy.